Wrong side of the leaf: assigning some Lithocolletinae species (Lepidoptera: Gracillariidae) to their proper genera - Eiseman, Charles S.; Davis, Donald R. (Zootaxa, 2020)
Cameraria Chapman and Phyllonorycter Hübner (Gracillariidae: Lithocolletinae) are two speciose genera of leaf-mining moths that were once treated as belonging to a single genus, Lithocolletis Hübner. Typically, species of Cameraria form flat mines on the upper leaf surface, whereas most Phyllonorycter species form underside tentiform mines. We reviewed North American literature records and found 15 exceptions to this generalization, with two Cameraria species reported to form underside mines and 13 Phyllonorycter species reported to form upper-surface mines. For each of these species we summarize the published data on larval biology, hostplants, and distribution, which we supplement with internet records and our own observations. Both purported Cameraria species making underside mines were misplaced in this genus by Davis (1983); we affirm the combinations Phyllonorycter affinis (Frey & Boll) and P. leucothorax (Walsingham), each of which has been published once before but not formally proposed as a new combination, and thus has been ignored by subsequent authors. We have further determined P. affinis to be a junior synonym of P. mariaeella (Chambers). Three of the purported Phyllonorycter species making upper-surface mines were similarly misplaced. One of these, Anarsioses aberrans (Braun), has recently been transferred to a new genus, and we propose the new combinations Cameraria arizonella (Braun) and C. cretaceella (Braun) for the other two. Genitalia and forewing patterns are illustrated for all species whose generic placement is corrected in this paper.